Reconceptualizing the archaeology of Southern India - Johansen, Peter G., author. Link
1 online resource
Keywords: "This book presents a paradigm shift in the long-term study of South India's deep history, one that refuses the disciplinary constraints of history and prehistory, and interrogates the archaeological and textual records of the Deccan to disrupt its conventional archaeological periodizations, which have tended to reify and dehistoricize social and cultural differences. This book draws on over 20 years of original archaeological research from the southern Deccan region of India to critically reappraise the historiography that has framed its deep history. The book fundamentally questions conventional archaeological paradigms, which rooted in early colonial scholarship, have structured interpretations of deep time with curiously ahistorical narratives of the past. It offers a more nuanced assessment of change and continuity across a diversity of cultural, social, and political practices through the novel application of theoretical framings to archaeological and historical data, including political ecology, techno-politics, resource materialities, and landscape production. It will be appropriate as a text in a range of graduate and undergraduate classes on archaeological method and theory and South Asian studies, where it will be a paradigm disrupting book for the archaeology and history of the region. This book will interest an interdisciplinary audience of graduate and undergraduate students and professional academics, primarily in the fields of archaeology, history, and South Asian studies. Its theoretical interventions will also be of interest to those interested in the anthropology and the archaeology of politics, chronology, historicity and historiography, and materiality and landscape archaeology"--